The Impact of Training in Soy Bean Seed Processing Towards The Change of Farmer’s Perception on Soybean Crop Farming at The Village of Kualeu, The Sub District of Sputh Amanatun, The District of Southern Middle Timor - Yutina Angela; Serman Nikolaus; Maria Bano (Undana Press, 2022)
It is known that the interest of farmers in South Amanatun Sub District on the soy bean crop farming had decreased. To return the farmer’s interest on this farming, then on the dates of 15 to 17 of July in 2019 had been runned a training program for farmers related to soy bean seeds processing to become tempe, tofu, and soy bean milk. The aim of this training program was to thange the farmer’s perception on the soy bean crop farming in a positive way. To find out whether or not this aim was achieved, a study had been carried out with the objectives of: (1) to find out farmer’s perception on soy bean crop farming, before and after training; and (2) to analyze the significant change of farmer’s perception after running the training. This study was used a sample with size of 37 farmers, selected randomly from the population of 60 farmers who participated in the training program. Related to objective 1, data were analyzed by the application of such descriptive statistics as: mean score, frequencies, percentage, and distribution table; while for the objective 2, data were analyzed by the use of Wilcoxon Pairs Ranking Test. Results of data analysis indicated that: (1) farmer’s perception on the soybean farming before conducting the training program was in “good enough category” because the percentage value of the farmer’s perception mean score in reaching the maximum score was 54.05% , while after conducting the training program the farmer’s perception was in “ good category” with the percentage value of farmer’s perception mean score in reaching the maximum score was in 72.0%; and (2) after conducting the training of soybean cultivation and seed processing technique had been done, the farmer’s perception on soy bean crop farming was changed significantly, where the probability value (p) of counting Z with the value of 4.8 was 0.0006, far lower than the α value of 0,01.